The Impact of Labor Market Entry Condition on Initial Job Assignment, Human Capital Accumulation, and Wages - Beatrice Brunner; Andreas Kuhn (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2010)
We estimate the effects of labor market entry conditions on wages for male individuals first entering the Austrian labor market between 1978 and 2000. We find a large negative effect of unfavorable entry conditions on starting wages as well as a sizeable negative long-run effect. Specifically, we estimate that a one percentage point increase in the initial local unemployment rate is associated with an approximate shortfall in lifetime earnings of 6.5%. We also show that bad entry conditions are associated with lower quality of a worker's first job and that initial wage shortfalls associated with bad entry conditions only partially evaporate upon involuntary job change. These and additional findings support the view that initial job assignment, in combination with accumulation of occupation or industry-specific human capital while on this first job, plays a key role in generating the observed wage persistencies.
Keywords: E3; J2; J3; J6; M5; 330; initial labor market conditions; endogenous labor market entry; initial job assignment; specific human capital